Գետնանուշի նոր սորտերի մշակության համեմատական արդյունավետությունը Հայաստանի նախալեռնային գոտում - Մաթևոսյան, Լ. Գ.; Բարբարյան, Ա. Ա.; Ավետիսյան, Ս. Գ. (ՀԱԱՀ հիմնադրամ)
В Армении арахис является нетрадиционной бобовой культурой, выращивается на небольших земельных участках, его средняя урожайность обеспечивается в пределах не более 19-20 ц/га. Предлагаем осуществлять выращивание арахиса в предгорной зоне Арагацотнской области, что даст возможность расширить его ареал, а также испытывать новые сорта. Groundnut is a nontraditional leguminous crop for Armenia. It is cultivated in small land areas and provides maximum 19 c/ha-20 c/ha yield capacity on the average. It is recommended to implement the groundnut cultivation in the sub-mountainous zones of the Aragatsotn region which will enable to enlarge its cultivation areal and to test some new varieties.
Keywords: Ագրոնոմիա և ագրոէկոլոգիա